Marker assisted selection (MAS) of spring bread wheat to improve productivity, grain quality, resistance to diseases and drought in the conditions of Western Siberia - S. S. Shepelev; I. V. Pototskaya; A. S. Chursin; A. I. Morgunov; V. P. Shamanin (Зерновое хозяйство России)
The challenges at the modern consumer market, climate change, an increase in the number of epiphytotic and arid years dictate the necessity to accelerate wheat breeding for a whole range of traits and, above all, those associated with an improvement of productivity, grain quality, resistance to diseases and drought. Marker assisted selection (MAS) allows reducing time for developing varieties with specified parameters in the conditions of a particular region. The purpose of the current work was to identify KASP-markers associated with genes of valuable traits in the collection and breeding material of wheat and effective SNP-loci for marker assisted selection (MAS) in Western Siberia. Identification of genes that control economically valuable traits using 64 KASP-markers in 2020 was performed in the LGC-Genomics laboratory (Great Britain). It was found that the platforms for genotyping SNP-loci of a large number of current varieties had a significant similarity, despite the geographical separation of varieties, which indicated the vulnerability of grain production during large-scale epiphytoties and drought. There have been found differences in the identified SNP-loci and their frequency of occurrence between current varieties, ancient wheat varieties, and breeding material based on synthetic wheat. According to the results of phenotyping of the studied samples in the field seasons of 2020–2021 there has been shown a significant effect of the root system’s parameters (genes TraesCS2D01G395500.1 and TraesCS4D01G341800.1 in chromosomes 2D and 4D) on grain size and productivity improvement. The drought resistant gene TaDreb-B1 has affected on an increase of grain content of a head and productivity. The genes GPC-B1 and TraesCS2D01G316300.1, which are responsible for nitrogen remobilization, protein and dry biomass accumulation in grain, significantly contributed to the improvement of nutritional grain value and accumulation of protein in grain. Due to marker-controlled selection in the CVT, there have been identified the varieties that significantly exceeded productivity standards, with a complex of genes that have positive effects on grain quality, resistance to diseases and drought.